Расчет объема требуемых сетевых ресурсов для предоставления услуг интерактивного телевидения - Евлаш, Д. В. (ХНУРЭ, 2009)
Now there is an active design and implementation of multiservice networks. One of the stages of design is the calculation of the required network resources for service delivery. Interactive TV services consumes a significant portion of network resources, which can not be neglected.
Keywords: сетевой ресурс; интерактивное телевидение